KAJIAN YURIDIS PENGELOLAAN DANA DESA DI DESA BUNGKO LOR KECAMATAN KAPETAKAN KABUPATEN CIREBON - Carkim Carkim; Abdul Wahid; Rohadi Rohadi; Siti Alisah (Jurnal De Jure Muhammadiyah Cirebon, 2021)
Ideally, the allocation of village funds is sought so that its management can be efficient and effective in the directions for which the funds are given. So the allocation of the Village Fund is a manifestation of the fulfillment of the village's right to carry out its autonomy, to realize the growth and development of Bungko Lor Village, Kapetakan District, Cirebon Regency, and to obtain financing in the form of a budget to carry out authority and at the same time support the implementation of good development. The purpose of this study is to determine the management of village funds and the obstacles in managing village funds in Bungko Lor Village, Kapetakan District, Cirebon Regency. The results of this study are as follows: 1. The management of Bungko Lor village funds, Kapetakan District, Cirebon Regency is to see the priority of using village funds to finance the implementation of programs and activities in the field of Village Development and Village Community Empowerment. The technical mechanism for managing village funds refers to the Cirebon Regent Regulation Number 25 of 2015 concerning Village Financial Management, starting from the stages of planning, implementation, reporting and accountability. 2. The management of village funds in Bungko Lor Village, Kapetakan District, Cirebon Regency has obstacles in implementation, namely a) Human resources that are not yet reliable and incompetent in managing village finances; b) low self-reliance of village communities; c) Direct community supervision by the community in managing village funds in Bungko Lor village has not yet occurred; d) community participation is very weak, sometimes it is carried out only unilaterally; e) Community understanding there are still many people who do not understand and do not know the use of village funds. Keywords: Juridical Study, Management, Village Fund.